Nawuri-Gonja Conflict, 1932-1996 - Mbowura, C.K. (University of Ghana, 2012)
This study examines the causes of the Nawuri-Gonja conflict, which broke out in 1991 over allodial land rights. In Alfai, as is the case of other Ghanaian societies, the modes of measuring allodial land rights are embedded in the historical traditions of the people. By right of autochthony and autonomy, allodial land rights in Alfai in the pre- colonial period resided in the Nawuri. However, Alfai’s encounters with the colonial enterprise led to the evolution of new constructs of allodial rights in land, which challenged established traditions and provided the opportunity for the immigrant Gonja community to appropriate land. In 1913 the Germans issued a warrant to Kanankulaiwura Mahama Karatu, the Gonja head chief in Alfai then, making him the overlord of the area for the sake of political expediency. This began Gonja rule over the Nawuri, which was made irreversible when the British colonial authorities subsumed Alfai into the Gonja kingdom in 1932 following the introduction of indirect rule in the Northern Territories. This led to series of encounters between the autochthonous Nawuri and their Gonja overlords over allodial rights in land, which expressed itself in social, political and economic debate in Alfai in the colonial and post-colonial times. By the dawn of independence, Alfai continued to remain as an integral part of the Gonja Traditional Area, thus strengthening Gonja claim that the land belonged to them. As the Nawuri and the Gonja continued to jostle each other over allodial land rights in Alfai in the post-colonial times, and as the dispute remained unresolved, war between them became a possibility. This study argues that the conflicting claims over allodial land rights in Alfai between the Nawuri and the Gonja served as the nexus that connected the multiplicity of layers of issues that underlay the conflict.
Thesis (PhD) - University of Ghana, 2012
Keywords: Conflicts; Security; Land Rights; Ghana